2009
DOI: 10.1017/s0950268809990410
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of common respiratory viral infections related to climate factors in hospitalized children in Hong Kong

Abstract: Hong Kong has a subtropical climate and an influenza seasonality lying approximately mid-way (March-June) between those of the Northern (November-March) and Southern (June-September) hemispheres. Respiratory syncytial virus (RSV) shares a similar seasonality to that of influenza in Hong Kong and is another important respiratory infection of childhood. Daily virus incidence data from public hospitals in Hong Kong's New Territory East Cluster, together with Hong Kong climate data were obtained for 2000-2007. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
4
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 54 publications
5
66
4
1
Order By: Relevance
“…In tropical settings lower respiratory infections in children are generally found to be more common during periods of higher rainfall and humidity, consistent with our results [7][8][9][10][11] . Rainfall is not convincingly associated with pneumonia incidence in time series studies from temperate settings 10,12,13 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In tropical settings lower respiratory infections in children are generally found to be more common during periods of higher rainfall and humidity, consistent with our results [7][8][9][10][11] . Rainfall is not convincingly associated with pneumonia incidence in time series studies from temperate settings 10,12,13 .…”
Section: Discussionsupporting
confidence: 92%
“…Low sunlight and temperature are consistently associated with high pneumonia incidence in time series studies in temperate settings, where annual peaks of lower respiratory infections occur during the short days of winter 10,[12][13][14][15][16] . The association between temperature and respiratory infections in children is inconsistent in time series studies from tropical settings, suggesting temperature is unlikely to be an important driver of pneumonia incidence in the tropics [6][7][8][9][10][11] . Less evidence examining the association of respiratory infection and sunlight exists from tropical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, each of the socioeconomic variables including population proportions of high school graduates (aged >25 years), percentage of persons living in poverty, and median household income were not significantly related to hospitalization rates. Second, mean county temperatures and dew point temperatures were not significantly related to hospitalization rates, which is inconsistent with other studies claiming that host immune responses are adversely sensitive to cold and dry climates (Lowen et al 2007;Tang et al, 2010). Finally, all race/ethnicity variables were not significantly related to county hospitalization rates, which is inconsistent with the majority of hospitalizations being Hispanic at the individual level.…”
Section: Discussioncontrasting
confidence: 84%
“…Since many influenza studies have found climatic factors to be related to influenza transmission (see Tang et al, 2010), it would be reasonable to consider climatic effects in human influenza transmission rates. Therefore, climatic variables were included using county mean temperatures and mean dew point temperatures (°C) constructed by averaging each county's weather station records between the months of April and September 2009 obtained via the Prism Climate Group.…”
Section: (D-f)mentioning
confidence: 99%